The Relationship Between Illicit Coca Production and Formal Economic Activity in Peru - Pedroni, Peter; Verdugo Yepes, Concha (Washington, D.C. : International Monetary Fund, 2011)
This paper investigates the relationship between unrecorded economic activity associated with the production of illicit coca and formally recorded economic activity in Peru. It does so by attempting to construct new regional level estimates for coca production and by implementing recently developed panel time series methods that are robust to regional heterogeneity and unobserved regional inter-dependencies. The paper finds that on balance illicit coca production crowds out formal sector production at the regional level, regardless of whether unanticipated changes occur nationally or regionally. However, total output nevertheless increases, since formal sector production is crowded out less than one for one.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet